PENGEMBANGAN PROGRAM COMMUNITY DEVELOPMENT CENTER SEBAGAI BAGIAN PERAN HUMAS PT. TELKOM WITEL SOLO - Artarini, Dara (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2023)
PT Telkom Witel Solo as part of public relations carries out the role of corporate social responsibility or CSR. The role of services and supporting programs responsible for MSME's program activities, namely the community or fostered partners. This activity program is a company program to help and be responsible for improving the economy in the Solo and surrounding areas. The objective of this study was to determine the development of the community development center program as part of the public relations role in PT. Telkom Witel Solo. This research was descriptive qualitative. The primary data were the results of interviews with the Witel Solo community development center employees. The results indicated that the development of community development center programs in the form of community relations, community service,and community empowering. The role of the community development center in program development was part of the role of public relations.